Moisture and temperature effect on soil phosphorus availability - Zalba, Pablo (2007)
The effect of desiccation temperature upon soil phosphorus availability was evaluated under laboratory conditions in soil samples of different texture. Soil samples of 1.4 g were weighed in 25 mL glass tubes and desiccated in an oven at 40, 60, 80 and 100o C using 2 different moisture levels: dry and wet. A total of 10 treatments were carried out with two replicates per treatment. Soil variables analyzed were: extractable phosphorus (Pe), organic phosphorus (Po), pH, organic carbon (OC), soil microbial activity (SMA), CaCO3 and texture (sand, silt and clay %). A marked increase in Pe was observed through the combined effect of moisture and temperature. Medium- and fine-textured soils showed higher Pe increments than coarser-textured soils. Whereas in medium-textured soils (loam) the increment in Pe varied between 4 mg kg-1 and 8 mg kg-1 as a result of the effect of temperature and temperature plus moisture, respectively, in the case of fine- and coarse-textured soils (clay loam and loamy sand) the increment was between 1 mg kg-1 and 6 mg kg-1. The soil variable analysis did not show any statistically significant relationships for Pe. However, high correlations were found between Po and SMA (r = 0.73, P <0.01) and between SMA and silt content (r = 0.86, P <0.01) . Thus, the results infer that soil microorganisms play an active role in the process of Po mineralization and the consequent increase in Pe.